Women on the labour market: historical trends and gender inequalities - Sawicka, Janina; Savytska, Nataliia; Polevych, Kateryna (Przegląd Wschodnioeuropejski, 2025)
The paper explores gender disparities in the global labour market through historical and contemporary perspectives, addressing the challenges and progress in female labour force participation. It highlights systemic barriers such as gender norms, discrimination, and contextual constraints, emphasizing the economic benefits of narrowing gender gaps. Utilizing frameworks like the Gender Employment Gap Index and data from the World Economic Forum’s Global Gender Gap Reports, the study examines regional and temporal variations in gender equality. Particular attention is paid to the situation of women in Europe, including Poland and Ukraine. A review of the world literature helps highlight the importance of a historical perspective in economic empirical research. Historical insights reveal the influence of socio-economic systems and cultural norms, while recent case studies – such as Ukraine during wartime – illustrate shifts in female economic roles. The paper underscores the critical role of integrated policy measures – from education and healthcare to childcare provision – in achieving economic gender parity.